Novice Teachers in Chile: Elt Teaching Capability Development and Social (In)Justice Awareness in Educational Marginalization - Romero-Villarroel, G (Routledge, 2024)
The Chilean system is known worldwide for the detrimental effect of neoliberal policies on public education and school segregation (Bellei et al. 2022). Drawing on Sen’s Capability Approach (1999), this paper examines how novice teachers of English balance the tension between the constraints of the social and educational systems (unfreedoms) to develop agency and transform challenges into English-language teaching opportunities (capabilities), and how they develop social (in)justice awareness to become helpful, caring, and committed ELT practitioners in their school communities. Data collected through open-ended surveys and semi-structured interviews reveal that novice teachers understand and question systemic unfreedoms (social, institutional, market-driven educational constraints) and social (in)justice in Chilean education and ELT. Such reflections allow them to distance themselves from curricular mandates, to develop ELT capabilities based on the academic and emotional needs of their learners, and intertwine English teaching with affective care and commitment to their schools’ educational projects and the wellbeing of marginalized students. © 2023 Taylor & Francis Group, LLC.